Education and employment: the key to women empowerment - Antony, Vaisamma (2006)
Empowering women socio-economically through increased awareness of their rights and duties as well as access to resources is a decisive step towards greater security for them. Women are in for a new deal today as they are the focus of economic development. All possible steps are being taken to strengthen them to achieve their economic, social, cultural and political growth and welfare.
Keywords: Employment; Education; Womens employment; Womens education